Fabrication of cefuroxime-impregnated calcium sulfate: Polycaprolactone composite implant for osteomyelitis - Gupta, Himanshu; Anand1, Anubhav; Pundir, Rakesh; Pandian, C S; Saraf, Shubhini (Asian Journal of Pharmaceutics (AJP), 2014)
Osteomyelitis is characterized as an inflammatory bone disease caused by pyrogenic bacteria. As oral bioavailabilities of antibiotics are low, a regimen of 6 weeks of intravenous antibiotic is necessary for adequate therapy. Although the dose of antibiotic administered systemically is high, therapeutically effective drug concentrations are not always achieved at the site of infection. This problem can be overcome by the use of local antibiotics from a biodegradable implant for chronic osteomyelitis that can deliver the drug at least for 6 weeks.The implant delivers high antibiotic concentration at tissue levels, obliterates dead space, aids bone repair and does not need to be removed. The aim of this study was to develop and evaluate a calcium sulfate and polycaprolactone (PCL)-based composite biodegradable implantable delivery system of cefuroxime for the localized treatment of osteomyelitis that can deliver the drug for at least 6 weeks.The PCL and calcium sulfate composite system has not been studied yet. Interaction studies were carried out to check any incompatibility between the ingredients. Implants were prepared by a modified fabrication technique to avoid solvent use. The prepared implants were evaluated for various in vitro parameters like dimensions, hardness, tensile strength, drug release profile, sterility test and morphological changes in pellet before and after drug release. The pellets were also tested for microbiological efficacy and compared with a plain drug solution in different concentrations. Developed pellets are regular in shape and size with good tensile strength. The release profile displayed drug levels above the minimum inhibitory concentration continuously for up to 2 months. A wide zone of inhibition by the pellet against Staphylococcus aureus as compared with the drug solution proves its efficacy in the treatment of osteomyelitis. Results show that the developed calcium sulfate and PCL-based composite biodegradable implantable delivery system of cefuroxime is a good alternate system and can deliver the drug for more than 6 weeks, maintaining an adequate inhibitory concentration at the site.